Asymmetric Total Synthesis of (−)‐Englerin A through Catalytic Diastereo‐ and Enantioselective Carbonyl Ylide Cycloaddition. Issue 33 (15th July 2015) - Hanari, Taiki; Shimada, Naoyuki; Kurosaki, Yasunobu; Thrimurtulu, Neetipalli; Nambu, Hisanori; Anada, Masahiro; Hashimoto, Shunichi
Abstract An asymmetric total synthesis of the guaiane sesquiterpene (−)‐englerin A, a potent and selective inhibitor of the growth of renal cancer cell lines, was accomplished. The basis of the approach is a highly diastereo‐ and enantioselective carbonyl ylide cycloaddition with an ethyl vinyl ether dipolarophile under catalysis by dirhodium(II) tetrakis[N‐tetrachlorophthaloyl‐(S)‐tert‐leucinate], [Rh2(S‐TCPTTL)4], to construct the oxabicyclo[3.2.1]octane framework with concomitant introduction of the oxygen substituent at C9 on the exo‐face. Another notable feature of the synthesis is ruthenium tetraoxide‐catalyzed chemoselective oxidative conversion of C9 ethyl ether to C9 acetate.